FEMALE ACCESSORY GLANDS WITH THEIR PROBABLE HOLE IN A SYRPHID FLY, ERISTALIS ARVORUM FABR. - SAREEN, M. L.; GILL, AMANJIT; BISWAS, S.; GILL, KAUR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1988)
Female E. arvorum possesses a pair of accessory gland which is tubular and highly branched structure opening into the genital chamber at its antero-lateral walls. Each accessory gland cell functions as a unit gland and comprises a large round or oval shaped reservoir which stores the secretory material and has an efferent ductule through which the secretions are channeled into the lumen of the gland. The lumen is lined by culticular intima. The secretion of accessory gland is mainly proteinous with only traces of carbohydrates. Glands have thus supplementary function in storing the spermatozoa but their secretions are mainly helpful in protecting the eggs and attaching them to the substrate as the glands are empty after oviposition.